Sonographic measurement of splenic length in children at Cipto Mangunkusumo Hospital - H F Wulandari; Kemas Firman (Indonesian Pediatric Society Publishing House, 2016)
Objectives The aim of this study was to determine the 10 th and 90 th percentiles and medians of normal splenic lengths of Indone- sian children at Cipto Mangunkusumo Hospital by ultrasonogra- phy using a method introduced by Rosenberg et al . Methods The maximum splenic length was obtained in longitudi- nal coronal plane with the splenic hilum visualized. The age of the patients were recorded. The medians and 10 th and 90 th percen- tiles for each age group were determined. Results Sixty-nine boys and 46 girls were examined at our institu- tion. The youngest subject was one month old and the oldest was 15 years old. The 10 th percentile, median, and 90 th percentile splenic length in the 1-3 months age group were 3.421 cm, 3.795 cm, and 4.343 cm, respectively. In the 3-6 month age group these measurements were 3.689 cm, 4.29 cm, and 5.094 cm, respec- tively; in the 6-12 month age group 4.016 cm, 4.72 cm, and 5.366 cm, respectively; in the 1-2 years age group 4.558 cm, 5.04 cm, and 5.502 cm, respectively; in the 2-4 year age group 5.151 cm, 6.225 cm, and 6.816 cm, respectively; in the 4-6 year age group 5.774 cm, 6.415 cm, and 7.82 cm, respectively; in the 6-8 year age group 6.077 cm, 7.505 cm, and 8.228 cm, respectively; in the 8-10 years age group 6.354 cm, 7.77 cm, and 8.602 cm, respectively; in the 10-12 years age group 6.354 cm, 7.77 cm, and 8.602 cm, respectively; and in the 12-15 year age group 7.934 cm, 9 cm, and 9.919 cm, respectively. In all age groups, the 10 th percentiles, medians, and 90 th percentiles were smaller than those of Ameri- can children as reported by Rosenberg et al. Conclusion The normal splenic lengths of Indonesian children are smaller than those of American children as reported by Rosenberg et al.